Frogs flee from the sound of fire. - Grafe, T Ulmar (2002)
Fire has an important role in the sensory ecology of many animals. Using acoustic cues to detect approaching fires may give slow-moving animals a head start when fleeing from fires. We report that aestivating juvenile reed frogs (Hyperolius nitidulus) respond to playbacks of the sound of fire by fleeing in the direction of protective cover, where they are safe. This is a novel response to fire not known to occur in other animals. Moreover, we identify the rapid rise-time of the crackling sound of fire as the probable cue used. These results suggest that amphibian hearing not only has evolved through sexual selection, but also must be viewed in a broader context.